Assessing and Treating Patients With Neuropathic Pain. Issue 11 (12th November 2015) - Scholten, Paul M.; Harden, R. Norman
Abstract: Neuropathic pain (NP) is a significant source of suffering, disability, and impairment, as well as an enormous cost to society. Historically, pharmacologic treatment has been limited to drugs approved for other conditions, including anticonvulsants, antidepressants, antiarrhythmics, and opioids, but in the past 2 decades several drugs have been approved by the Food and Drug Administration specifically for NP. Understanding the underlying pathophysiology and clinical presentation of the various causes of NP states facilitates a rational selection of pharmacologic, interventional, rehabilitative, and psychological options for reducing pain and maximizing function.